Overview of The Incidence and Risk Factors for Nosocomial Infections Using a Geographic Information System Maps - Setianto, Rochady; Lazuardi, Lutfan; Dahesihdewi, Andaru (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2013)
Hospitalized patients have a high risk of getting nosocomial infections due to various reasons. They tend to be more susceptible to infection because oftheir underlying disease condition, and they have higher when patients undergo invasive procedures. If the patient’s immune system is impaired, thenon-pathogenic microorganism are capable of causing disease. Map is a method of illustrating an epidemiologic effectively . Maps can be used to showplace of incidence. Mapping the incidence of nosocomial infections in Sultan Agung Hospital is a method developed for the surveillance of nosocomialinfections. This type of research is a quantitative study with a cross sectional design. This study illustrates the risk factors of nosocomial infection withincidence of nosocomial infections that occur based on time point. Risk factors are extrinsic and intrinsic factors. Based on the spatial image on the map,in extrinsic incidence of nosocomial infections is Plebitis. Genesis Plebitis incidence correlates with the placement of hand washing points handrub. Whilethe intrinsic factor in the Plebitis image and ILO most inpatient distribution in patients aged 50 years with impaired skin integrity due to infusion andphysically due to decreased immunity associated with a variety of underlying diseases. Incidence of nosocomial infections in the inpatient unit is theprimary predisposing factors such as age and clinical issues related predisposing underlying disease can weaken the immune system of the patient, so thatthe procedures and even the most basic medical treatment could potentially cause nosocomial infection.